Prevalence, Virulence, and Antimicrobial Resistance of Major Mastitis Pathogens Isolated from Taiwanese Dairy Farms - Dhital, Bigya; Chuang, Shih-Te; Hsieh, Jui-Chun; Hsieh, Ming-Hsiu; Chiang, Hsin-I (Antibiotics (Basel), 2024)
Mastitis, a highly prevalent disease in dairy cows, is responsible for massive financial losses due to decreased milk yield, milk quality, and costly medication. This research paper investigates antimicrobial susceptibility in cows and the role played by both resistance and virulence gene distribution in bovine mastitis. A total of 984 raw milk samples were collected from five different dairy farms and cultured on sheep blood agar plates. Antimicrobial susceptibility was determined by disc diffusion, and corresponding resistance and virulence genes were detected by PCR. Among the collected milk samples, 73, 32, and 19 isolates of Streptococcus spp., Staphylococcus spp., and coliforms were identified, respectively. The antimicrobial susceptibility results showed that Streptococcus spp. were resistant to tetracycline (86.30%), neomycin (79.45%), and oxacillin (73.97%). Staphylococcus spp. were resistant to tetracycline (59.37%) and oxacillin (53.12%). Lastly, coliforms were resistant to oxacillin (100%) and bacitracin (68.42%). The genotyping results showed that Streptococcus spp. carried the resistance genes tetM (46.57%) against tetracycline, bcrB (41.09%) against bacitracin, and aph(3)-II (39.72%) against neomycin. Staphylococcus spp. carried the resistance genes bcrB (40.62%) and tetM (18.75%), and coliforms carried the resistance genes tetM (42.10%) and bcrB (57.89%). Moreover, 57.53%, 75.0%, and 63.15% of Streptococcus spp., Staphylococcus spp., and coliforms carried lmb, fib, and ompC virulence genes, respectively. All three tested bacterial genera showed no significant association between antimicrobial resistance genes and virulence factors, although they were negatively correlated (p > 0.05). The combination of resistance gene identification and susceptibility tests as components of the diagnosis of bovine mastitis can help in selecting effective antimicrobial agents to treat it.